Orotracheal intubation without the use of muscle relaxant: Propofol or etomidate in combination with remifentanil (2009)
Introduction: Remifentanil followed by propofol provides adequate conditions for tracheal intubation without using muscle relaxants. Other hypnotic drugs have not been thoroughly evaluated in this regard. The purpose of this study was to assess intubating conditions and cardiovascular changes after induction of anesthesia with remifentanil-propofol or. Methods: 90 ASA I/II patients were enrolled in this random, prospective, double-blind study. Subjects received 0.03 mg/kg of midazolam followed by a 7 ml/kg infusion of Ringe?s lactate. After that, 3 ?g/kg of remifentanil were injected followed by lydocaine, 1 mg/kg. Then, patients received either propofol (2 mg/ kg) (Propofol Group, n= 29), or etomidate (0.3 mg/kg) (Etomidate 3 Group, n=31) or etomidate (0.4 mg/kg) (Etomidate 4 Group, n=30). Subsequent laryngoscope and intubation were performed. Intubating conditions were assessed using a quality scoring system. Mean arterial pressure and heart rates pre-induction, post-induction were recorded immediately after intubation and every 1 to 5 minutes after intubation. Results: Three patients in the etomidate 3 Group and two patients in the etomidate 4 Group were not able to be intubated in the first attempt. Clinically acceptable intubating conditions were observed in 100%, 74%, 80% in the Propofol, Etomidate 3 and etomodate 4 groups, respectively (p=0.01 6). The decrease in mean arterial pressure was significantly higher in the propofol group as compared to the etomidate 3 group (p less than 0.05). Conclusions: The use of lydocaine-remifentanil-propofol for tracheal intubation without muscle relaxants is superior to 0.3 or 0.4 mg/kg lydocaine-remifentanil plus etomidate. However, etomidate 0.3 mg/kg produces a better hemodynamic profile when compared to propofol.